(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the multifaceted impact of social media on young people, examining both the positive and negative effects. It highlights how social media platforms serve as tools for communication, self-expression, and community building, enabling youth to connect with peers and access information. However, it also addresses concerns related to mental health, cyberbullying, and the pressure to maintain an idealized online persona. The article emphasizes the importance of fostering digital literacy and healthy online habits among young users to mitigate risks while maximizing the benefits of social media engagement